Electromagnetic Materials and Devices 2020
DOI: 10.5772/intechopen.82483
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Losses of Microwave Ceramics Based on Crystal Structure

Abstract: So far, many microwave dielectric materials have been investigated for a range of telecommunication applications. In dielectrics, the three main dielectric properties are quality factor (Q), dielectric constant and temperature coefficient of resonant frequency. Among these, the most essential dielectric property is Q. More specifically, Q is the inverse of the dielectric loss (tanδ); thus Q = 1/tanδ. There are two kinds of losses: those depending on crystal structure and losses due to external factors. The for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Generally, this behavior can be explained by the characteristics of the ε r that is influenced by ionic or electronic polarization, which generates α d in the presence of electromagnetic wave 27 . The increasing value of ε r provides a higher α d value as the electric field intensity inside the dielectric layer increases 23 .…”
Section: Andmentioning
confidence: 99%
“…Generally, this behavior can be explained by the characteristics of the ε r that is influenced by ionic or electronic polarization, which generates α d in the presence of electromagnetic wave 27 . The increasing value of ε r provides a higher α d value as the electric field intensity inside the dielectric layer increases 23 .…”
Section: Andmentioning
confidence: 99%
“…The PDF-2 database for 2004 contains three diffraction spectra of the Ва 6 Ta 2 O 11 compound (Table 1). A fragment of the phase diagram of the BаO-MgO-Ta 2 O 5 system given in [4] is shown in Fig. 1, where it is indicated that the compound is a metastable phase and can be used as a microwave dielectric [1,4].…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
“…A fragment of the phase diagram of the BаO-MgO-Ta 2 O 5 system given in [4] is shown in Fig. 1, where it is indicated that the compound is a metastable phase and can be used as a microwave dielectric [1,4].…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Several silicate-based materials such as Mg 2 SiO 4 , MgSiO 3 , ZrSiO 4 , Cu-doped Mg 2 SiO 4 , and Zn 2 SiO 4 are well known for substrate application at microwave frequency range. [6][7][8][9] However, most of these materials cannot be used for LTCC because of their high sintering temperature. There are some known strategies for reducing the sintering temperature of these materials, which include the addition of low-melting-point glasses or the addition of lowmelting-point oxides, which can be employed in order to use these materials for LTCC application.…”
Section: Introductionmentioning
confidence: 99%